Examining the Impact of Limited-Time Offers on Consumer Purchase Behavior in Online Shopping Platforms - Baybayon, Ann Magdalene; Parungao, Ralph Jay; Rivera, Kathlyn Mae; Salvador, Lovely Krizzel; Vega, Noemi (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examines the influence of limited-time offers (LTOs) on online consumer behavior, focusing on purchase intention, impulse buying, and perceived product value. Grounded in behavioral and psychological theories—particularly the principles of urgency, scarcity, social proof, and perceived value—the research explores how these mechanisms shape decision-making in digital commerce environments. A descriptive research design was employed, with data collected through an إلكترonic survey questionnaire distributed via Google Forms to online shoppers aged 18 and above in San Isidro, Nueva Ecija. Using convenience sampling, responses were analyzed through descriptive statistics and a 4-point Likert scale to determine levels of influence. Findings indicate that LTOs moderately influence consumer behavior, with social proof emerging as the strongest psychological driver, significantly affecting purchase decisions through reviews, ratings, and peer influence. Fear of Missing Out (FOMO), scarcity, and urgency also contributed to increased impulsive buying, faster decision-making, and enhanced perceived value, though to a moderate extent. Results further reveal a balance between impulsive and rational decision-making, as consumers often compare prices despite time pressure and may experience post-purchase regret. Demographically, younger and lower-income consumers were more engaged in online shopping and responsive to LTOs. The study concludes that while LTOs are effective marketing tools for increasing engagement and sales, excessive or misleading use may lead to promotion fatigue, reduced trust, and diminished brand credibility. It recommends that businesses adopt ethical, transparent, and personalized LTO strategies while leveraging verified social proof and responsible data practices. The study aligns with Sustainable Development Goals (SDG) 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation and Infrastructure), and SDG 12 (Responsible Consumption and Production), as it enhances understanding of digital marketing practices and consumer decision-making in e-commerce. Its sustainability impact lies in promoting responsible marketing strategies, informed consumer behavior, and ethical digital commerce practices that support long-term trust and economic sustainability.
Keywords: E-Commerce; Fear of Missing Out; Impulse Buying; Limited-Time Offers; Perceived Value; Purchase Intention; Scarcity; Social Proof